Design and Fabrication of Lifting Beam for Air Pre Heater Centre Section Parts - R, Manjunathan; N, Gayathri; M, Muralidharan; A, Barathan; R, Delhibabu; T, Ilaiyarasu (International Journal of Engineering and Technology, 2018)
The project deals with the reduction of using multiple cranes during the lifting of the Centre section parts and introducing a new system called lifting beam. The lifting beam is designed to carry a weight of 18- 20tons with the self weight of 2-2.5 tons ,reducing the involvement of more number of employees and eliminating the unwanted processes like gas cutting and welding during multiple crane usage, which results in making the Air pre heater (APH) to preheat the fresh Atmospheric air which takes the heat from outgoing Exhaust gas. APH is the device to improve the efficiency that is used generally in the thermal power plants, the main aim of this project also lies in making the lifting beam the versatile one which must be used for both the types of the centre section parts i.e., both the type of pre heaters that are being manufactured in the company of different power capacity of respective length 16 and 18 meters.Â Â